2020
DOI: 10.1038/s41380-020-00878-1
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine modulates fronto-striatal circuitry in depressed and healthy individuals

Abstract: Ketamine improves motivation-related symptoms in depression but simultaneously elicits similar symptoms in healthy individuals, suggesting that it might have different effects in health and disease. This study examined whether ketamine affects the brain’s fronto-striatal system, which is known to drive motivational behavior. The study also assessed whether inflammatory mechanisms—which are known to influence neural and behavioral motivational processes—might underlie some of these changes. These questions were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 77 publications
(139 reference statements)
3
53
0
Order By: Relevance
“…Decreased connectivity was identified, after ketamine in healthy volunteers. Increased connectivity between the dorsal caudate and the ventromedial prefrontal cortex, 2 days and 10 days after ketamine, also correlated with a reduction in anhedonia in the MDD group ( Mkrtchian et al, 2020 ).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Decreased connectivity was identified, after ketamine in healthy volunteers. Increased connectivity between the dorsal caudate and the ventromedial prefrontal cortex, 2 days and 10 days after ketamine, also correlated with a reduction in anhedonia in the MDD group ( Mkrtchian et al, 2020 ).…”
Section: Resultsmentioning
confidence: 96%
“…The drug effects on brain connectivity seem to persist even longer than 24 h since the decrease in the connectivity between the DMN and the insula that was identified for MDD patients compared to HCs was smaller 48 h after ketamine administration but returned to baseline 10 days past the ketamine infusion ( Evans et al, 2018 ). Ketamine produced increases in the connectivity of striatal regions ( Mkrtchian et al, 2020 ) with the dorsolateral and ventrolateral PFC, the pregenual ACC and the OFC in depressed individuals, while decreases were observed for the same set of brain regions in healthy volunteers. Moreover, the increases and decreases in the connectivity of the amygdala and the hippocampus also lasted for more than 24 h and were detectable after multiple ketamine infusion ( Vasavada et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Human neuroimaging studies also demonstrated ketamine related changes in functional connectivity across the frontostriatal circuitry. For example, a recent study showed increased functional connectivity between the caudate and PFC regions (dlPFC and vlPFC), and between the putamen and PFC regions (more specifically perigenual ACC and the orbitofrontal cortex) in treatment-resistant depression (TRD) patients [74]. However, in healthy volunteers, ketamine reversed these functional connectivity effects.…”
Section: Nmda Modulation Of Habenula Neurons Might Be Orchestrating the Expression Of Anhedonia Across Fronto-mesolimbic And Fronto-striamentioning
confidence: 99%
“…The observed lack of difference in the action of 15 and 18 in the MK-801 impaired NORT may look bizarre. However, there have been reports of paradoxical actions of glutamatergic drugs such as different outcomes in healthy individuals and patients [ 33 , 34 ]. The observed similar effects of compounds 15 and 18 in NORT could possibly be related to the restored BDNF levels described by Rychtyk et al [ 20 ].…”
Section: Discussionmentioning
confidence: 99%